Development of Local Wisdom Product Bamboo Furniture, in Mae Hong Son Province - ไชยนันท์, ไชยเชิด; กิตติพัฒนวิทย์, เจษฎาพล; ศักดิ์สง่า, นภมินทร์; รินแสงปิน, มนัสพันธ์ (Community and Social Development Journal, 2019)
This research aims to 1) study patterns of bamboo product in Mae Hong Son province 2) design, develop, and create prototypes of bamboo furniture based on identity of Mae Hong Son province 3) deliver knowledge about furniture design principles to the community and exchange knowledge between researchers and bamboo furniture producers group in Mae Hong Son province 4) study the opinion and satisfaction of producers in Mae Hong Son about bamboo furniture prototypes, which were co-developed from researchers and the community. This mixed methods research was a participated work, between researchers and community, to develop products. The process was included document study and fieldwork to find the demand of producers and markets. This research used survey research and experimental research methods to reach all necessary data to develop bamboo furniture. Questionnaires were used with 100 samples to evaluate satisfaction about the developed bamboo furniture. Moreover, this research found that most of the furniture materials came from local area and nearby communities. From five times of fieldworks, this research found that producer group interested in the development for their own products in a good level. The research found that there was only one pattern of bamboo furniture in the province and the group which was in Baan Kong area of Mae Sarieng district. The pattern had been created from customer’s demand without concept of beauty idea so the design was plain and focused only on the ease of use. Their technique and process were inherited from predecessors and daily life style. The evaluation score of satisfaction on nine new developed products were in a good level.